The temporality of style in exposition architecture: Raimondo d'Aronco in context and comparison - Rugare, Steven (ARCC Conference Repository, 2014)
Since the early twentieth century "style” has been particularly suspect in relation to architecture. A tendency to cross out the word "style” in architecture continues today in the self-presentation of many younger architects. Speaking generally, the crossing out of "style” was at first a reaction to the pre-1914 modernists. In this regard the work of Italian architect Raimondo d'Aronco is instructive. This paper argues that his stylistic inventions at the 1902 Decorative Arts Exposition in Turin, in which ephemeral construction methods and a unique program associated with modern decorative art led him to devise a hybrid that only existed in built form for six months. Critical responses were mixed, but this isn't a sign of failure, given that the buildings were both evidence of and containers for very current debates about the meaning of "modern” design in Italy. D'Aronco's work suggests the validity of an approach to modern styles drawn from actor-network theory. Instead of concentrating on a defining set of formal principles or visual ticks, "style” is understood here as a material stabilization of controversies, as a set of visual traits that increase the density of connections between materials, technologies, and stories about social groupings. To further explore this idea, the paper looks briefly at two much more famous modernist examples, Mies' German Pavilion and Le Corbusier's Philips Pavilion, each of whichs hows a different approach to the architect's role as an actor within the networked context of a large exposition.